A proposed training program to qualify teachers of Arabic for non-native speakers on the uses of augmented reality technology to teach students at the Institute for Teaching Arabic to Non-Native Speakers in the Islamic University - AlHarbi, Abdullah AbdulMuhsen; Almelhes, Sultan Abdulaziz; AlMailabi, Bandar Salah (Dirasat: Human and Social Sciences, 2024)
Objectives: The current research aims to determining the level of cognitive knowledge of faculty members and teachers at the Institution for Teaching Arabic to Non-Native Speakers at the Islamic University of Madinah, including theoretical and practical aspects of computer and AR technologies uses in teaching Arabic to non-native speakers, and training needs to AR technologies. It also aims to recognizing the content of the training program and its duration. Methods: The research employed the descriptive methodology. Its tool was (the questionnaire), which was distributed to the population, numbering (52) academics and teachers, (47) responded. Results:. The results exhibited a very high level of faculty members in using the computer in teaching Arabic to non-native speakers, arithmetic mean is (4.23), with a standard deviation of (0.66). They revealed deficiencies in the cognitive part related to the uses of AR among faculty members. The targeted use of AR applications in teaching Arabic to non-native speakers is weak, as (82.98%) of them had never used AR applications. They also ensured a training need among the target audience on the uses of AR technologies in teaching Arabic to non-native speakers. The research also determined the content and duration of the needed AR training program. Conclusions: There is a need to training program on AR uses for teaching Arabic language for non-native speakers. The academics and teachers at Arabic language institude of Islamic university need not less than two days training including theoritical and practical aspects of using AR in teaching the language.